(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Organisational culture refers to the shared values, beliefs, attitudes, norms, and behaviors that exist within an organisation. It encompasses the way people within the organization interact, communicate, and work together. Here are some key points about organizational culture. • Values and Vision: Organizational culture is influenced by the core values and vision of the organization. These values reflect what the organization deems important and guide the behavior and decision-making of its members. • Norms and Working Language: Organizational culture establishes the norms, or accepted behaviors, within the organization. It includes the working language, communication styles, and unwritten rules that shape how people interact and collaborate. • Systems and Processes: Culture is also reflected in the systems, processes, and structures of an organization. It encompasses the way tasks are assigned, decisions are made, and work is organized. • Symbols and Artifacts: Symbols and artifacts, such as logos, slogans, office layout, and physical environment, contribute to the expression and reinforcement of organizational culture. These visible elements often represent and communicate the values and identity of the organization. • Beliefs and Habits: Organizational culture is shaped by the collective beliefs and assumptions held by its members. These beliefs influence how individuals perceive and interpret situations, make judgments, and behave within the organization. • Socialization and Learning: Organizational culture is transmitted to new members through socialization processes. New employees learn about the values, norms, and expected behaviors through formal orientation programs, informal interactions, and observation of their peers and superiors. • Impact on Interactions: Organizational culture influences how people and groups interact within the organization. It affects communication patterns, collaboration, teamwork, decision-making processes, and the overall working environment. External Interactions: Organizational culture also extends to interactions with clients, customers, suppliers, and other external stakeholders. It shapes the organization’s reputation, customer service approach, and external relationships. Understanding and managing organizational culture is important as it can have a significant impact on employee morale, productivity, engagement, and ultimately, the organization’s success. Organizations may strive to cultivate a positive and inclusive culture that aligns with their values and supports their strategic objectives.